Engineering uniform nanocrystals: Mechanism of formation and self‐assembly into bimetallic nanocrystal superlattices. Issue 2 (14th October 2015) - Cargnello, Matteo; Doan‐Nguyen, Vicky V. T.; Murray, Christopher B.
Abstract : The preparation of metal nanocrystals (NCs) with precise and tunable size is of great interest for many applications. Following previous reports on the synthesis of monodisperse nickel, palladium, and platinum NCs, we here show that the narrow size distributions are the result of an optimized combination of surfactants that play a dynamic, synergistic role in stabilizing the particles at different stages (nucleation, growth) of their preparation. This dynamical process allows the temporal separation of nucleation and growth responsible for the narrow size distributions achievable with this heat‐up method. Finally, the uniform NCs are exploited in the preparation of binary nanocrystals superlattices entirely based on metal components, with promising applicability in the fields of catalysis, sensing, and optics. © 2015 American Institute of Chemical Engineers AIChE J, 62: 392–398, 2016